Elektryczne modelowanie sprężystego podłoża - Lisowski, A. (Engineering Transactions, 1969)
The author presents three models of an elastic foundation and the corresponding electric systems. The adjustment of the foundation is represented by the current, the deflection by the voltage and the elastic constants by electric resistances. The foundation is treated, of necessity, as a set of points interconnected by elastic links.